Managing for Quality in the Hospitality Industry - John H. King; Ronald F. Cichy (New Jersey Pearson Prentice Hall, 2006)
This practical Quality Management book focuses on meeting the expectations of internal customers, external customers, and owner/investors-the backbones of any organization and its culture. Integrating theories and real-life examples to illustrate how to achieve high quality, the authors add credibility to the process by sharing their successful quality management experience in a contemporary case history - while simplifying the most important elements in managing quality in the hospitality industry. Chapter topics cover how to tap an organization's hidden strengths, team effectiveness, the tools of the trade, assessing and implementing quality, leadership, and quality life. For Managers of Quality, General Managers, owners, executives and other personnel in the hotel, restaurant, and club industries.
Keywords: Total quality management; Quality control; Hospitality industry; (MASB-2903) Service Quality Management in Tourism and Hospitality